O laicato na Conferência Episcopal Latino-Americana de Medellín (1968) - Scopinho, Sávio Carlos Desan (Revista eclesiástica brasileira, 2013)
This article studies the understanding of the Ecclesiastical Magisterium of the Catholic Church about the laity in the second Latin American Episcopal Conference held in Medellin, Colombia, in 1968. At that conference there was an attempt to systematize and define the role of the laity inside the Church and society, resuming the intuitions of the Second Vatican Council (1962-1965) and the view of the Latin American Ecclesiastical Magisterium. So, the proposal is to offer a diachronic and synchronic view about the theme, having the focus on the conclusive document of the Medellin Conference referring the laity issue. It’s also necessary to take in account the Conference subsequent historical entailments, especially at the XIV CELAM Assembly, held in Sucre, Bolivia, in 1972. Therefore, the aimis to demonstrate, in a critical and systematic perspective, that the layman has had a historical and doctrinal development in the Latin American Ecclesiastical Magisterium view, always with many challenges and fragilities, but also with hopes and possibilities at the same time. The Catholic Church in Latin America has experienced a historical and doctrinal context of ambiguities and contradictions since the Second Vatican Council, without losing the Christian ideal that is based on a fair, supportive and committed society with the option for the poor. The laity is called to have consciousness about that reality and to accept his responsibility before the challenges present in the own Church structure and in the relationship with society as well. In this ecclesial and social context, we must not neglect the importance of the Medellin Conference, since it has a doctrinal and pastoral contribution to the laity, which will be resumed later in the conclusive documents of the Episcopal Latin American Conferences in Puebla (1979), Santo Domingo (1992) and Aparecida (2007).Keyword: Latin American Bishops, Conference of Medellín, Laity